Slipinskiscymnus gen. nov., a new ladybird genus of Scymnini (Coleoptera, Coccinellidae) and notes on the taxonomic status of Keiscymnus Sasaji - Peng, Feng; Poorani, J.; Booth, Roger G.; Wang, Xingmin; Chen, Xiaosheng; Anuradha, C. (Zootaxa, 2023)
Slipinskiscymnus gen. nov. (Coleoptera: Coccinellidae) is proposed to accommodate two anomalous species of Scymnini, namely, Scymnus pallidicollis Mulsant, 1853 (= Slipinskiscymnus pallidicollis (Mulsant), comb. nov.) and Scymnus saciformis Motschulsky, 1858 (=Slipinskiscymnus saciformis (Motschulsky), comb. nov.) and five new species, Slipinskiscymnus confertus Peng et Chen sp. nov., S. siculiformis Peng et Chen sp. nov., S. spiculatus Peng et Chen sp. nov., S. interstricus Peng et Chen sp. nov. and S. keralensis Poorani sp. nov., described from China and India. A lectotype is designated for Scymnus saciformis Motschulsky, 1858 (lectotype designation). Descriptive accounts of these species with illustrations of adult habitus, male genitalia and other diagnostic characters are given with a key to species. Notes on the status of the genus Keiscymnus Sasaji, 1971, are also provided.